THE EFFECT OF SELF-CONTROL AND SELF-REGULATION ON FEAR OF MISSING OUT (FOMO) IN STUDENT USERS OF TIKTOK SOCIAL MEDIA - Fitra Andini; Hasan Hasan; Ikhlas Rasido; Azam Arifyadi (SOSIOEDUKASI, 2026)
This study aimed to analyze the influence of self-control and self-regulation on Fear of Missing Out (FOMO) among students who use TikTok social media in East Palu District, Palu City. This study employed a quantitative approach with an ex post facto design and multiple linear regression analysis. The sample consisted of 250 students who were active TikTok users and were selected through questionnaire distribution. Data were collected using self-control, self-regulation, and FOMO scales that had met validity and reliability requirements. The results showed that self-control and self-regulation simultaneously had a significant effect on FOMO (p < 0.05). Partially, self-control did not have a significant effect on FOMO (p = 0.189), whereas self-regulation had a significant effect on FOMO (p = 0.000). These findings indicate that self-regulation plays a more dominant role in influencing the level of FOMO among students who use TikTok. Students with higher self-regulation tend to manage their social media use more effectively and are therefore less likely to experience FOMO. The findings imply the importance of strengthening students’ self-regulation skills through guidance and counseling services as an effort to reduce FOMO tendencies among TikTok users.